A Novel Form of RNA Polymerase from Escherichia coli - Wickner, William (1974)
A new form of RNA polymerase, termed RNA polymerase III, has been recognized as a large fraction of the rifampicin-sensitive enzyme in E. coli. It is physically separable from RNA polymerase (holoenzyme, RNA polymerase I) by gel filtration and is distinguished by its capacity to discriminate between M13 and ϕX174 viral DNA templates in priming DNA synthesis. This template specificity is manifested only with saturating levels of DNA unwinding protein and characterizes the priming of DNA synthesis on viral single strands in cell-free extracts and in vivo. RNA polymerase III has less than 5% of the specific activity of RNA polymerase I in transcribing duplex DNA of phages λ and T4, salmon sperm DNA, and the copolymer poly[d(A-T)]. Rifampicin inactivation of RNA polymerase III releases a factor, presumably a small subunit, which can be isolated and used to confer on RNA polymerase I the properties of III, namely, discrimination between M13 and ϕX174 templates in priming DNA synthesis, and a relative inability to transcribe duplex DNA.